2011
DOI: 10.3174/ajnr.a2810
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Laryngopyocele: CT-Guided Hookwire Localization for Re-Excision Surgery

Abstract: SUMMARY: Laryngopyocele recurrence after initial surgical resection is a very rare occurrence. We present a case of recurrent laryngopyocele in which CT fluoroscopyϪguided hookwire placement was used to facilitate resection. In this article, we illustrate the imaging findings of laryngopyocele, review the approach to management, and describe the CT fluoroscopyϪguided hookwire placement procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The use of ultrasound or CT‐guided hookwire in cervical surgery was recently reviewed 27,28 and several studies reported its use in resection of benign or malignant lesions 11,29–42 . There are only four reported cases of lateral cervical adenectomy using US‐guided hookwire localization 37–39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ultrasound or CT‐guided hookwire in cervical surgery was recently reviewed 27,28 and several studies reported its use in resection of benign or malignant lesions 11,29–42 . There are only four reported cases of lateral cervical adenectomy using US‐guided hookwire localization 37–39 .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The use of ultrasound or CT-guided hookwire in cervical surgery was recently reviewed 27,28 and several studies reported its use in resection of benign or malignant lesions. 11,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] There are only four reported cases of lateral cervical adenectomy using US-guided hookwire localization. [37][38][39] Park et al reported a series of eight cases of preoperative ultrasound-guided hookwire needle localization of nonpalpable cervical mass.…”
mentioning
confidence: 99%